A Navigation Ranging Scheme With True Random Entangled Microwave Signals - Xiang Li; Dewei Wu; Qiang Miao; Haonan Zhu; Tianli Wei (IEEE Photonics Journal, 2018)
Focusing on the problem of vulnerable anti-deception and weak anti-jamming ability in classical pseudorandom code correlation ranging, we present a navigation ranging scheme with true random entangled microwave signals. One path of the entangled microwave signals uses for transmitting signal and another path of the signals preserves at locality. Firstly, the target that possesses the function of quantum repeater receives transmitting signal and forwards it to the locality. Then, correlation detection is implemented between the forwarded signal and the local delayed signal. Finally, the target distance can be calculated by delay measurement. We analyze the ranging precision and anti-deception ability. Results indicate that the scheme not only is superior to classical code correlation ranging precision, but also has very strong anti-multipath ability and anti-multipath interference ability, which will enhance the security of the navigation ranging system. Our investigation has significant application prospects.